2019
DOI: 10.11646/zootaxa.4585.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The type specimens of Trichomycterus alternatus (Eigenmann, 1917) and Trichomycterus zonatus (Eigenmann, 1918), with elements for future revisionary work (Teleostei: Siluriformes: Trichomycteridae)

Abstract: The trichomycterid catfish species Trichomycterus alternatus (Eigenmann, 1917) and Trichomycterus zonatus (Eigenmann, 1918) are reportedly among the most pervasive species in mid- to high-elevation coastal streams of Southeastern Brazil. Despite their apparent abundance and ecological ubiquity, the applicability of their names is still uncertain. Examination of the type material of the two species reveals that part of the confusion stems from a mixing of species in the T. zonatus type series. Other issues rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 476 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Despite that, species of Trichomycterus are still being described at a fast rate, especially from Southeastern Brazil. Many of such descriptions are presented with little regard for intraspecific and geographical variation, known to be pronounced in species of the genus, and often with no information from critically‐important type material, especially from older names (Reis & de Pinna, ). While some of those species are certainly valid, overall such practice has added to the taxonomic confusion and increased the backlog of potential synonyms to be sorted out in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, species of Trichomycterus are still being described at a fast rate, especially from Southeastern Brazil. Many of such descriptions are presented with little regard for intraspecific and geographical variation, known to be pronounced in species of the genus, and often with no information from critically‐important type material, especially from older names (Reis & de Pinna, ). While some of those species are certainly valid, overall such practice has added to the taxonomic confusion and increased the backlog of potential synonyms to be sorted out in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In all examined species of Trichomycterus , the epioccipital is a flat bone with smooth and rounded contours. The same is true for the few species where this cranial element has been described or illustrated ( T. alternatus (Eigenmann 1917) in Reis & de Pinna, : fig. 4, p. 108; T. areolatus , T. gracilis Valenciennes 1846, T. nigricans , T. punctulatus Valenciennes 1846, and T. rivulatus Valenciennes 1846 in Arratia, : figs.…”
Section: Discussionmentioning
confidence: 68%
“…Molecular results confirm the recent hypotheses by other authors (Donin, ; Reis & de Pinna, ) that Trichomycterus alternatus was equivocally identified as T. zonatus (= Cambeva zonata ) in collections as well as in the literature (Menezes et al , ; Oyakawa et al , ). Consequently, some putative occurring localities of C. zonata cited in the literature ( e.g ., Lima, ; Wosiacki & Oyakawa, ) are refuted and correspond to T. alternatus .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, T. alternatus seems to have a wide distribution and found in several isolated drainages of south and southeast Brazil, extending from Paranaguá Bay tributaries to the Doce River basin(Donin, 2019). Other authors argued that T. alternatus is likely part of a species complex that may include other nominal species, needing an extensive revision(Lima, 2009, erroneously cited as F I G U R E 9 Colouration in live specimens from two ontogenetic stages of (a) Trichomycterus alternatus (UFRGS 24540, 57.2 and 40.9 mm L S , tributary of Guaraqueçaba River, Paranaguá Bay), and (b) Trichomycterus jacupiranga (UFRGS 24555, 44.8 mm L S and 35.1 mm L S , córrego do Queimado, Ribeira de Iguape River basin) Trichomycterus zonatus;Reis, 2018;Reis & de Pinna, 2019). In the samples of T. alternatus (see "Comparative Material Examined") analysed here, no diagnostic morphological differences were observed, and there is also little genetic structuration (seeSupporting Information Tables S3 and S4) when comparing samples from Paranaguá Bay tributaries, Ribeira de Iguape River and coastal rivers in the state of São Paulo.…”
mentioning
confidence: 99%